Phytophthora cactorum : A Diagnostic Guide for Foliar Blight and Root Rot of American Ginseng - Abdelrazek Abdelrhim; Santosh Koirala; Ethan Tippett; Mary K. Hausbeck (Plant Health Progress, 2026)
Phytophthora cactorum is an important pathogen that can infect more than 200 plant species. It causes Phytophthora foliar blight and root rot on several economically important Panax species. Infected plants display dark green, water-soaked foliar blight lesions, reddened and wilted foliage, hollowed stems, and soft and spongy roots. P. cactorum is phylogenetically distinct, but morphological similarities exist among Phytophthora species. This diagnostic guide describes P. cactorum, its taxonomic status, host range, and geographical distribution, as well as symptomology of Phytophthora foliar blight and root rot on American ginseng (Panax quinquefolius), methods of P. cactorum isolation, morphological and molecular identification, storage, and pathogenicity tests on different hosts.